Facile synthesis of 3D flower-like Cu2−xSe nanostructures via a sacrificing template method and their excellent antibacterial activities. Issue 48 (27th November 2017) - Zhu, Lianjie; Gao, Fubo; Lv, Pengzhao; Zeng, Yan; Wang, Wenwen; Zheng, Wenjun
Abstract : The flower-like Cu2− x Se assembled from hexagonal nanosheets shows excellent antibacterial activities to S. aureus and E. coli, and its antibacterial mechanism was confirmed experimentally. Abstract : A three-dimensional (3D) flower-like Cu2− x Se film with a hexagonal nanosheet hierarchical structure has been synthesized for the first time from a 3D flower-like CuO film precursor through a facile sacrificing template method at room temperature. The product was characterized and its formation mechanism was explored using a series of control experiments combined with crystal structure analysis. The optical property and photodegradation activities of the Cu2− x Se film on three dye solutions were studied. Notably, its antibacterial activities were explored for the first time . The results show that the 3D flower-like Cu2− x Se is assembled from numerous hexagonal nanosheets with thicknesses of about 50 nm. The flower-like Cu2− x Se displays excellent antibacterial activities against both Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ). For the first time, the experimental results confirm that the antibacterial rate depends on the Cu(ii ) ion concentration which is closely related to the Cu2− x Se quantity and incubation time.